The importance of economic valuation for conservation in Lower Kinabatangan Segama Wetland, Sabah - Muhamad Ali, Abdul Hamid; Mohammad Afandi, Syamsul Herman; Shuib, Ahmad; Ramachandran, Sridar; Tukiman, Husin (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Lower Kinabatangan Segama Wetland consists of three Permanent Forest Reserve covered a total area approximately 78,803 Ha. Situated in the eastern coast of Sabah and manage by Sabah Forestry Department, LKSW has been designated as Ramsar Site in 2008. The natural ecosystem in LKSW comprised of mangrove and peat swamp vegetation, wet grassland on peat and brackish; it provides habitat to various species of fauna and flora. Villages within and adjacent to LKSW are also depends on the resources available for their livelihood and sustenance. The uniqueness of biodiversity attractions has its potential for ecotourism industry from local and international visitors. The resources in LKSW have its economic important in terms of market value and non-market value creating a significant need for economic assessment. Economic valuation is a powerful tool for quantifying economics importance of wetlands in conservation and development planning. It also aims to quantify the benefits that people obtain from the wetland ecosystem goods and services. This makes them comparable with other economy sector when investments are being appraised and activities are planned. Hence, limited information about wetland values, misallocation of resources substantially can be occurred and immense economic costs will often incurred. This paper will briefly highlight the importance of determination of market and non market value and valuation method approaches for LKSW.